Methyl-CpG binding domain proteins inhibit interspecies courtship and promote aggression in Drosophila - Tarun Gupta (Nature Portfolio, 2017)
Abstract Reproductive isolation and speciation are driven by the convergence of environmental and genetic variation. The integration of these variation sources is thought to occur through epigenetic marks including DNA methylation. Proteins containing a methyl-CpG-binding domain (MBD) bind methylated DNA and interpret epigenetic marks, providing a dynamic yet evolutionarily adapted cellular output. Here, we report the Drosophila MBD-containing proteins, dMBD-R2 and dMBD2/3, contribute to reproductive isolation and survival behavioral strategies. Drosophila melanogaster males with a reduction in dMBD-R2 specifically in octopamine (OA) neurons exhibit courtship toward divergent interspecies D. virilis and D. yakuba females and a decrease in conspecific mating success. Conspecific male-male courtship is increased between dMBD-R2-deficient males while aggression is reduced. These changes in adaptive behavior are separable as males with a hypermethylated OA neuronal genome exhibited a decrease in aggression without altering male-male courtship. These results suggest Drosophila MBD-containing proteins are required within the OA neural circuitry to inhibit interspecies and conspecific male-male courtship and indicate that the genetically hard-wired neural mechanisms enforcing behavioral reproductive isolation include the interpretation of the epigenome.